The Place of Legitimacy in Legal Theory - Priel, Dan (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2011)
In this essay I argue that in order to understand debates in jurisprudence one needs to distinguish clearly between four concepts: validity, content, normativity, and legitimacy. I show that this distinction helps us, first, make sense of fundamental debates in jurisprudence between legal positivists and Dworkin: these should not be understood, as they often are, as debates on the conditions of validity, but rather as debates on the right way of understanding the relationship between these four concepts. I then use this distinction between the four concepts to criticize legal positivism. The positivist account begins with an attempt to explain the conditions of validity and to leave the question of assessment of valid legal norms to the second stage of inquiry. Though appealing, I argue that the notion of validity cannot be given sense outside a preliminary consideration of legitimacy. Following that, I show some further advantages that come from giving a more primary place to questions of legitimacy in jurisprudence.